Optimal management of production processes using the function of losses in the production processes. Issue 1 (September 2020) - Kirov, K; Avramova, T
Abstract: In today's modern world the manufacturing processes are designed in such a way as to ensure the desired quality of the end product. In this article are considered some aspects of desired quality in performance. The described quality management tools are based on Taguchi's theory Quality Engineering and Robust Engineering. In relation to this in the paper are presented a new application for assessing the losses of society from the irrational use of resources or their harmful impact in the transformation into a production process, the possibilities of Taguchi's theory in assessing the losses of the stakeholders in the functioning of the enterprise - in case of ineffective or inefficient use of the production process and proposal of the possibility for a complex assessment of the losses of the society and the stakeholders from the production of products and operation of production processes at quality indicators different from the desired nominal values